Exploring the transfer of recent plant photosynthates to soil microbes: mycorrhizal pathway vs direct root exudation. Issue 4 (10th November 2014) - Kaiser, Christina; Kilburn, Matt R.; Clode, Peta L.; Fuchslueger, Lucia; Koranda, Marianne; Cliff, John B.; Solaiman, Zakaria M.; Murphy, Daniel V.
Summary Plants rapidly release photoassimilated carbon (C) to the soil via direct root exudation and associated mycorrhizal fungi, with both pathways promoting plant nutrient availability. This study aimed to explore these pathways from the root's vascular bundle to soil microbial communities. Using nanoscale secondary ion mass spectrometry (NanoSIMS) imaging and 13C‐phospho‐ and neutral lipid fatty acids, we traced in‐situ flows of recently photoassimilated C of 13CO2‐exposed wheat (Triticum aestivum) through arbuscular mycorrhiza (AM) into root‐ and hyphae‐associated soil microbial communities. Intraradical hyphae of AM fungi were significantly 13C‐enriched compared to other root‐cortex areas after 8 h of labelling. Immature fine root areas close to the root tip, where AM features were absent, showed signs of passive C loss and co‐location of photoassimilates with nitrogen taken up from the soil solution. A significant and exclusively fresh proportion of 13C‐photosynthates was delivered through the AM pathway and was utilised by different microbial groups compared to C directly released by roots. Our results indicate that a major release of recent photosynthates into soil leave plant roots via AM intraradical hyphae already upstream of passive root exudations. AM fungi may act as a rapid hub for translocating fresh plant C to soil microbes.